2019
DOI: 10.1111/efp.12561
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus, nitrogen and potassium nutrition on Calonectria leaf blight in eucalypt plants

Abstract: Calonectria pteridis causes Calonectria leaf blight (CLB), and consequently severe defoliation in eucalypt plantations, which results in losses in wood volume. To reduce the negative impacts of this disease in eucalypt, this study aimed to assess the application of different doses and combinations of the macronutrients N, P and K on the percentage of symptomatic leaf area (SLA) and defoliation induced by the pathogen. Cuttings of a clone of Eucalyptus grandis were transplanted to pots containing soil that rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Our study showed a strong correlation between disease severity percent on root and herb fresh weight assessed on main contents in leaves of moringa plants during the two experiments. These results are in line with those reported by Huber and Haneklaus (2007); Scurich (2012); Gupta et al (2017) and Zarpelon et al (2019). Mineral nutrients are the components of plants and regulate metabolic activity associated with resistance of a plant and virulence of a pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed a strong correlation between disease severity percent on root and herb fresh weight assessed on main contents in leaves of moringa plants during the two experiments. These results are in line with those reported by Huber and Haneklaus (2007); Scurich (2012); Gupta et al (2017) and Zarpelon et al (2019). Mineral nutrients are the components of plants and regulate metabolic activity associated with resistance of a plant and virulence of a pathogen.…”
Section: Discussionsupporting
confidence: 92%